An analysis of the post 1980s transition from pastoral to game farming in South Africa: a case study of the Marico district - Zulu, Nqobile (My University, 2016)
This thesis is an analysis of narratives of private game farming in Groot Marico. Through this case study, it argues that the material and symbolic processes of game farming and hunting depict a ‘colonial present’ in their constitution. Part of that ‘colonial present’ stems from ‘white privilege’, a legacy of South African history. A major part comes from the gate-keeping function of in-group beneficiaries represented by associations and networks. Race, class, language and capital are used to maintain the status quo. The situation has been aided by a state whose neo liberal policies support commercialisation more than social justice redress. The thesis traces the historical antecedents and the contemporary socio-economic and political factors that have led to white farmers’ conversion into game farming from domestic livestock production. Continuities of practices, from farm ownership to hunting have been processes that maintain the status quo. Yet white farmers have argued that these continuities are ‘tradition’, whether in hunting or game farming, while being silent on the lack of transformation of the industry. Despite the visibility of a few high-profile black personalities, the industry remains overwhelmingly white. I argue that the game farming community has created a ‘structure’ to which high-profile black figures can belong, not only as examples of transformation but primarily to protect vested interests by their token inclusion. Economic and political status has been the criteria upon which the few black figures have been ‘allowed’ into the group. In spite of the racial demographics, game farming is not homogenous as the Groot Marico case studies reveal. There are cleavages around the position of game farmers within the hierarchy of game farming, and these are informed by class. Trophy-hunters, meat producers, and small, marginal farmers all occupy different spheres within the game farming sector. The trophy hunter and game breeder are at the top of the hierarchy as opposed to the small one man game farmer surviving at the margins. The meat producer deals with the economics of supplying a niche market at a different level from the trophy game farmer and the small one man game farmer. Yet these three are bound together in an increasingly besieged farming community where land reform is a constant reminder of what can be lost. Other bonds of solidarity derive from a shared discourse of conservation that ties it to the maxim ‘if it pays it stays’. This economic tenet, describes the game farming community’s approach to wildlife conservation.
A thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy in the Faculty of Humanities at the University of Witwatersrand, Johannesburg.
Keywords: Private game farming; Conservation; South Africa; Neo liberalism; Race; Class; Colonial present